2017
DOI: 10.12786/bn.2017.10.e3
|View full text |Cite
|
Sign up to set email alerts
|

Current State and Prospects of Development of Blood-based Biomarkers for Mild Traumatic Brain Injury

Abstract: Highlights• There are many unresolved clinical problems about mild traumatic brain injury (mTBI) such as a low sensitivity of standard neuroimaging studies, and absence of reliable predicting models.• It is very difficult to diagnose mTBI in symptomatic patients in the absence of witnesses, clear signs of head trauma, and abnormalities on neuroimaging.• Blood proteins have great potential as diagnostic and prognostic biomarkers of mTBI.• Technological advances in the targeted proteomics are expected to realize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…GFAP is a protein found only in the central nervous system. GFAP levels are increased when astrocytes are damaged [ 30 ]. A low GFAP integral intensity indicates a decrease in reactive astrocytosis, which can play a neurotoxic role and aggravate neural death [ 31 , 32 ] Previous study showed that GFAP could determine patients with mTBI with subtle injuries detected only through MRI [ 33 ] 30 days after all treatments and evaluations (Day 36), 12 rats (3 rats from each group were randomly selected) were euthanized by carbon dioxide inhalation using an approved standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…GFAP is a protein found only in the central nervous system. GFAP levels are increased when astrocytes are damaged [ 30 ]. A low GFAP integral intensity indicates a decrease in reactive astrocytosis, which can play a neurotoxic role and aggravate neural death [ 31 , 32 ] Previous study showed that GFAP could determine patients with mTBI with subtle injuries detected only through MRI [ 33 ] 30 days after all treatments and evaluations (Day 36), 12 rats (3 rats from each group were randomly selected) were euthanized by carbon dioxide inhalation using an approved standard protocol.…”
Section: Methodsmentioning
confidence: 99%